FACTORS INFLUENCING THE USE OF FIELD TEACHING IN GEOGRAPHY - Džinović, Milanka (Metodička teorija i praksa, 2025)
This applied research aims to determine the factors that influence the prevalence of the application of field teaching as a form of extracurricular education in the implementation of geographical content from fifth to eighth grade, according to the opinion of 111 teachers in the Republic of Serbia, depending on their teaching experience and academic education. The elements of emancipatory didactics form the theoretical basis. The results indicate that there is still an insufficient number of geography teachers willing to implement this work. However, they know the numerous advantages of fieldwork, citing the time and effort required for organization. In contrast, teachers who use fieldwork highlighted it as the most interesting part of their teaching activities. The pedagogical implications of these findings point to the need for educational policy (number of lessons in curricula, etc.) to be dedicated to the possibility for teachers to have the conditions for this type of teaching activities in geography teaching.